Fabrication and mechanical characterization of glass fibre reinforced triaxially braided composites. (February 2021) - Marrivada, Gayatri Vineela; Chaganti, Phaneendra Kiran; Sujith, Ravindran
The aim of this research work is to study the mechanical behaviour of dry triaxially braided glass fibre sleeves and its composites experimentally and analytically. The braided glass fibre sleeves for three angles 30°, 45° and 60° were fabricated on a modified maypole vertical braider following a regular braid architecture. Tensile, flexural, short beam shear and impact tests were performed to evaluate the mechanical properties of the composites. A numerical model was developed, which can be used to find the elastic properties and mechanical strength values of the dry braided fabric and its composites. It was observed that the tensile, flexural and interlaminar properties of 30° specimens were more compared to 45° and 60°. The difference between the estimated and experimental values were found to be an average of 8% for tensile moduli and 24% for the tensile strength.